Emergency Heart Failure Mortality Risk Grade-7 Score Performance in Patients with Acute Heart Failure admitted at a Tertiary Care Center - Shrestha, Bikesh; Poudel, Chandra Mani; Gajurel, Ratna Mani (Journal of Institute of Medicine Nepal, 2024)
Introduction Heart failure is a major cause of morbidity and mortality worldwide with annual mortality of 8-9%. Acute heart failure patients require frequent Emergency Department visits and hospitalization.Emergency Heart Failure Mortality Risk Grade (EHMRG) score helps to risk stratify such patients. We aimed to study its performance at a tertiary care centre in Nepal. Methods This is an analytical, study involving 175 acute heart failure patients admitted at Emergency department over 1 year. The score was calculated for each patient and they were followed up for 30 days post discharge for readmission. The primary outcome studied was 7 day mortality. Results The median age was 66 years with 94 (53.7%) of the patients being male. Ischemic (38.3%) and dilated (25.1%) cardiomyopathies were the most common etiologies. Twenty seven (15.3%) of the patients required re-hospitalization within 1 month.There was statistically significant association (p<0.001) between 7-day mortality and high EHMRG scores (Class 5 and 4). No 7-day mortality was observed in the very low, low, and intermediate-risk groups. In the high-risk group (Class 4), 1 patient died while 15 survived. In the very high-risk group (Class 5), 29 patients died compared to 45 who survived. Conclusion Mortality within 7 days and readmission rates were higher in patients with high EHMRG scores. No mortalitites were encountered in patients with low scores. EHMRG can be a valuable tool to stratify acute heart failure patients as it can identify patients with high risk of 7 day mortality. It can help physician in deciding whether to discharge or admit the patients from Emergency rooms.